WHAT IS THE ROLE OF JOURNALISM IN THE POLITICAL ADVOCACY OF HEALTH POLICY IN INDONESIA? - Ridlo, Ilham Akhsanu (Universitas Airlangga, 2024)
In this short commentary article, the complex association between journalism, health policy, and political campaigning in Indonesia is explained, in need of more scholarly expansion. Within those limitations, the paper does alert to the necessary function journalism serves intrinsic to the public discourse that drives health policy recommendations, as well as noting how this has been perverted by misinformation and dwindling faith in the media. The article examines how journalism (including digital and social media) has shaped health policy advocacy and public opinion and highlights the role of the media in health communication campaigns and policy reform. Through scrutiny of its role in health policy advocacy, with a broader look at how journalism roles have shifted over time. In this article, the author demonstrated that journalism is a bridge between health policy experts and the public, enabling a more informed democratic engagement with health policy. These conclusions highlight the need to build a nexus between democratic journalism and health policy advocacy for public health priorities in Indonesia. Keywords: health policy, journalism, political campaign